Analisis Perbandingan Bunga Meihua dan Sakura yang Terlihat Sama Tetapi Berbeda - Yolanda Natalia; Rudiansyah Rudiansyah (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2021)
Flowers are one of the plants that are in great demand for cultivation or even just as decorations during certain celebrations. Meihua flowers and cherry blossoms are very beautiful flowers, not infrequently many can't tell the difference between these two types of flowers, because they really look the same. If you look closely, these two types of flowers are very easy to distinguish, starting from the shape, color and fragrance. This research uses qualitative descriptive by describing pictures of a natural phenomenon without any engineering or human intervention. From this study it can be clearly seen that the comparison between meihua flowers and cherry blossoms is the difference in the shape of the leaves, petioles, trees, flower petals and the resulting fragrance. but behind that there are benefits from this plant which is used for several purposes such as medicines and beauty products. In Chinese and Japanese beliefs, this plant also has different meaning and meanings.Keywords: meihua flower; cherry blossom; philosophy